2019
DOI: 10.1111/mice.12447
|View full text |Cite
|
Sign up to set email alerts
|

Vibration‐based structural state identification by a 1‐dimensional convolutional neural network

Abstract: Deep learning has ushered in many breakthroughs in vision‐based detection via convolutional neural networks (CNNs), but the vibration‐based structural damage detection by CNN remains being refined. Thus, this study proposes a simple one‐dimensional CNN that detects tiny local structural stiffness and mass changes, and validates the proposed CNN on actual structures. Three independent acceleration databases are established based on a T‐shaped steel beam, a short steel girder bridge (in test field), and a long s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(102 citation statements)
references
References 56 publications
0
86
1
1
Order By: Relevance
“…At present, deep learning methods are popularly applied for various applications. For example, damage identification on structures with images (Cha, Choi, & Büyüköztürk, 2017;Gao, Kong, & Mosalam, 2019;Gao & Mosalam, 2018;Li, Zhao, & Zhou, 2019;Ni, Zhang, & Chen, 2019;Wu et al, 2019;Yang et al, 2018), with sensor measurements (Huang, Beck, & Li, 2019;Y. Zhang, Miyamori, Mikami, & Saito, 2019), concrete property estimation (Rafiei, Khushefati, Demirboga, & Adeli, 2017), and vehicle type detection in real traffic data (Molina-Cabello, Luque-Baena, López-Rubio, & Thurnhofer-Hemsi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At present, deep learning methods are popularly applied for various applications. For example, damage identification on structures with images (Cha, Choi, & Büyüköztürk, 2017;Gao, Kong, & Mosalam, 2019;Gao & Mosalam, 2018;Li, Zhao, & Zhou, 2019;Ni, Zhang, & Chen, 2019;Wu et al, 2019;Yang et al, 2018), with sensor measurements (Huang, Beck, & Li, 2019;Y. Zhang, Miyamori, Mikami, & Saito, 2019), concrete property estimation (Rafiei, Khushefati, Demirboga, & Adeli, 2017), and vehicle type detection in real traffic data (Molina-Cabello, Luque-Baena, López-Rubio, & Thurnhofer-Hemsi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the computational cost for real-time image processing is expensive [ 31 ], while to the best knowledge of the author, there are few researches on the vehicle detection and classification based on DL using one-dimensional signal data. To inspire the methodology, one-dimensional CNN has already been utilized in damage detection based on vibration data [ 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…Avci et al [6] addressed the loss of connection stiffness of a steel frame structure via a novel structural health monitoring (SHM) method using 1DCNN and wireless sensors networks. Zhang et al [7] developed a 1DCNN method for VSHM of bridge structures and successfully tested on both a simplified laboratory model and a real steel bridge. Ince [8] demonstrated that the 1DCNN architecture was highly effective in real-time monitoring motor conditions because their model took only 1.0 ms per classification, and the experimental accuracy result was more than 97%.…”
Section: Introductionmentioning
confidence: 99%